PENGGUNAAN MEDIA INTERAKTIF WORDWALL UNTUK MENINGKATKAN HASIL BELAJAR OPERASI HITUNG PERKALIAN BILANGAN CACAH SAMPAI 1000 PADA SISWA KELAS V SD INPRES TARUS 1 - Adel Delilah Nenosaban (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
The purpose of this study was to improve the learning outcomes of fifth grade studentsby using wordwall learning media in mathematics learning at SD Inpres Tarus 1. Thisstudy used classroom action research consisting of four stages, namely planning,implementation, observation, and reflection. The methods used in this study weredescriptive qualitative and descriptive quantitative. Data collection techniques usedwere observation and testing. From the results of data analysis, it showed that theresults of observations of teacher activities in cycle 1, the teacher had mastered theclass but learning had not run optimally in cycle II, the learning process ran optimally.Then the results of observations of student activities in cycle 1 showed that studentswere not active in participating in learning activities and disturbed other friends. In cycleII, it was seen that students were already actively discussing and learning was runningoptimally. Student learning outcomes in cycle I obtained an average class score of66.92 with a learning completion percentage of 53.85% and in cycle II of 83.36 with alearning completion percentage of 88.46%. So it can be concluded that the use ofwordwall media can improve student learning outcomes.